2022
DOI: 10.3389/fchem.2022.865375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gallium as an Additive Over Corresponding Ni–Mo/γ-Al2O3 Catalysts on the Hydrodesulfurization Performance of 4,6-DMDBT

Abstract: Experiments were carried out to research the different contents of Ga2O3 modification effects on the hydrodesulfurization (HDS) performance of 4,6-dimethyldibenzothiophene (4,6-DMDBT) catalyzed by the stepwise impregnation method. Characterization techniques such as XRD, BET, HRTEM, NH3-TPD, and Py-FTIR were performed to determine the effects of each modification of the catalyst by Ga on the properties of the prepared supports and catalysts. The catalytic effect of gallium is reflected in the fact that the emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The bands at 1445 cm À1 , 1575 cm À1 , and 1604 cm À1 correspond to the Lewis acid sites. According to the literature, [40][41][42][43] the sharp bands at 1445 cm À1 and 1604 cm À1 are attributed to the strong interaction of pyridine with the Lewis acid sites, while the weak band at 1575 cm À1 indicates weak Lewis-bound pyridine. Furthermore, the peak at 1489 cm À1 corresponds to the combination of Lewis and Brønsted acid sides.…”
Section: Resultsmentioning
confidence: 95%
“…The bands at 1445 cm À1 , 1575 cm À1 , and 1604 cm À1 correspond to the Lewis acid sites. According to the literature, [40][41][42][43] the sharp bands at 1445 cm À1 and 1604 cm À1 are attributed to the strong interaction of pyridine with the Lewis acid sites, while the weak band at 1575 cm À1 indicates weak Lewis-bound pyridine. Furthermore, the peak at 1489 cm À1 corresponds to the combination of Lewis and Brønsted acid sides.…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, metal-support interaction is essential for electron transfer in catalysts prepared using multiple metals. Recently, there has been a rising concern about the use of additives such as Ga [26][27][28], P [29][30][31], Ti [32], Mg [33,34], and Ce [35,36] in the synthesis of desulfurization catalysts. These additives have been found to enhance the catalytic properties of the materials in which they were included [26,37].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a rising concern about the use of additives such as Ga [26][27][28], P [29][30][31], Ti [32], Mg [33,34], and Ce [35,36] in the synthesis of desulfurization catalysts. These additives have been found to enhance the catalytic properties of the materials in which they were included [26,37]. Previous literature has shown that the addition of gallium to the surface alters the morphology of promoted MoS 2 slabs, enhances the activity of NiMo catalysts, and directly affects the conversion rate and selectivity of DDS and HYD routes to some degrees [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation